Spore number control and breeding in Saccharomyces cerevisiae - Taxis, Christof; Bork, Peer; Stelzer, Ernst H. K.; Knop, Michael (The journal of cell biology, 2005)
Spindle pole bodies (SPBs) provide a structural basis for genome inheritance and spore formation during meiosis in yeast. Upon carbon source limitation during sporulation, the number of haploid spores formed per cell is reduced. We show that precise spore number control (SNC) fulfills two functions. SNC maximizes the production of spores (1-4) that are formed by a single cell. This is regulated by the concentration of three structural meiotic SPB components, which is dependent on available amounts of carbon source. Using experiments and computer simulation, we show that the molecular mechanism relies on a self-organizing system, which is able to generate particular patterns (different numbers of spores) in dependency on one single stimulus (gradually increasing amounts of SPB constituents). We also show that SNC enhances intratetrad mating, whereby maximal amounts of germinated spores are able to return to a diploid lifestyle without intermediary mitotic division. This is beneficial for the immediate fitness of the population of postmeiotic cells.
Gesehen am 17.08.2017